2016
DOI: 10.1111/resp.12735
|View full text |Cite
|
Sign up to set email alerts
|

Breathing‐related changes of respiratory resistance in vocal cord dysfunction

Abstract: Vocal cord dysfunction induced by exercise in children with uncontrolled asthma was identified by laryngoscopy. The paradoxical adduction of the vocal cords was also indicated by the breathing-related changes of the forced oscillation respiratory resistance showing prominent increase during inspiration and a large positive difference between inspiration and expiration. The breathing-related changes of respiratory resistance offer thus a useful first-line technique to diagnose vocal cord dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
(17 reference statements)
2
9
0
1
Order By: Relevance
“…60 As presented in the accompanying editorial, 60 a previous study utilizing a mechanical model of VCD, 61 demonstrated that the within breath respiratory resistance (Rrs) measured with FOT was significantly increased during inspiration. A similar observation was reported by Ioan et al 59 in children with VCD during exercise as Rrs was increased during inspiration when VCD was present. This phenomenon is not observed during breathing in healthy individuals or in those with asthma.…”
Section: Neil D Evessupporting
confidence: 87%
See 1 more Smart Citation
“…60 As presented in the accompanying editorial, 60 a previous study utilizing a mechanical model of VCD, 61 demonstrated that the within breath respiratory resistance (Rrs) measured with FOT was significantly increased during inspiration. A similar observation was reported by Ioan et al 59 in children with VCD during exercise as Rrs was increased during inspiration when VCD was present. This phenomenon is not observed during breathing in healthy individuals or in those with asthma.…”
Section: Neil D Evessupporting
confidence: 87%
“…58 Ioan et al 59 investigated the utility of FOT for the diagnosis of vocal cord dysfunction (VCD) in children. VCD is associated with the paradoxical adduction of the vocal cords and is commonly associated with, or mistaken for, asthma because of the similarity of symptoms.…”
Section: Neil D Evesmentioning
confidence: 99%
“…The respiratory resistance (Rrs) is measured non-invasively by the forced oscillation technique and may conveniently be used to describe the time course of airway caliber in relation with breathing, especially during prolonged observation. Acute patterns have been described in children where the exercise-induced paradoxical vocal cord motion had otherwise been authenticated by laryngoscopy (3, 4). In this paper, we present a coordinated characterization of exercise-induced paroxysmal dyspnea.…”
mentioning
confidence: 99%
“…In an attempt to face this problem, Ioan et al . carried out a pilot study published as Scientific Letter in this issue of Respirology . These authors focused on exploring the potential of using the forced oscillation technique (FOT) for easily and non‐invasively assessing upper airway obstruction along the breathing cycle.…”
mentioning
confidence: 99%
“…As resistance can be computed from each individual oscillation cycle, FOT provides high‐time resolution in tracking airway obstruction along the breathing cycle, which is of major interest for assessing VCD. For instance, a resistance value is obtained every 83 ms for a FOT frequency of 12 Hz, as in the work by Ioan et al …”
mentioning
confidence: 99%